MAKING A DIFFERENCE IN THE LIVES OF YOUNG CHILDREN: A CRITICAL ANALYSIS OF A PEDAGOGICAL DISCOURSE FOR MOTIVATING YOUNG WOMEN TO BECOME EARLY CHILDHOOD EDUCATORS - Langford, Rachel (Canadian Journal of Education/Revue canadienne de l’éducation, 2008)
Findings in this article indicate that training programs use a key pedagogical and ideological discourse of “teachers make a difference” to motivate female early childhood education students to enter and stay in the field. However, research in the area of workforce retention maintains that many graduates are not willing to enter and stay in a workforce characterized as economically, socially, and politically marginalized, and part of a secondary labour market. This article, which presents an alternative pedagogical discourse to account for the realities of the work, could initiate changes in professional identity formation, social relations, and economic arrangements. Key words: training, workforce, marginalization retention Cet article résume les conclusions d’une recherche selon lesquelles des programmes de formation se servent d’un discours pédagogique et idéologique du slogan : « les enseignants font la différence » en vue d’inciter des étudiantes en éducation de la petite enfance à s’engager dans ce domaine et à y rester. Or, des recherches sur le maintien de l’effectif démontrent qu’un grand nombre de diplômées ne veulent pas entrer et à rester dans un domaine qui regroupe une main‐d’œuvre marginalisée économiquement, socialement et politiquement et faisant partie d’un marché secondaire de l’emploi. Cet article, qui présente un autre discours pédagogique rendant compte des réalités du travail, pourrait favoriser l’introduction de changements dans la formation de l’identité professionnelle, les relations sociales et les modalités économiques. Mots clés : formation, main‐d’œuvre, marginalisation, maintien de l’effectif